Phosphorus fractions in Oxisols - Silva, Meire Adélia da; Nóbrega, Júlio César Azevedo; Curi, Nilton; Siqueira, José Oswaldo; Marques, João José Granate de Sá e Melo; Motta, Paulo Emilio Ferreira da (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to verify if the historical use, phosphorus fertilization, mycorrhizal inoculation and cultivation with brachiaria and soybeans in greenhouse alter P fractions in three Oxisols. P linked to Al (P-Al), Fe (P-Fe), and Ca (P-Ca) were determined. The P fractions were separated with resin, NaHCO3, NaOH, HCl, and digestion with H2SO4 and H2O2. The organic and inorganic fractions were separated by autoclaving. In the cohesive Yellow Latosol (LAx) and acric Red Latosol (LVw), the P-Al, P-Fe, and P-Ca were higher in the cultivated soils, and in the dystroferric Red Latosol (LVdf), the P-Al and P-Fe were higher in the non-cultivated soils, trends non-altered by the cultivation with brachiaria and soybeans. P addition elevated mainly the labile inorganic (Pi-resin and Pi-NaHCO3) and the moderately labile (Pi-NaOH) fractions. Soils formerly cultivated presents less P in the organic fractions than the non-cultivated ones. In soils with brachiaria, less P in the less labile fractions and more P in the more labile ones were verified. The effect of mycorrhizae was smaller and less consistent than the cultivation and P application.
Keywords: Brachiaria decumbens; Glycine max; phosphate fertilizers; mycorrhizal fungi